POLA INTERAKSI SOSIAL MAHASISWA DALAM PROSES KOMUNIKASI BELAJAR E-ELEARNING KULINO - Andika Eko Prasetyo (Program Studi Ilmu Komunikasi FISIP UM Buton, 2023)
Coronavirus Disease 2019 or Covid-19, entered Indonesia indonesia since early 2020. This has an impact on the activities to experience restrictions, including the aspects of Teaching and Learning Activities (KBM) in Higher Education. Based on the Joint Decree of the 4 Ministers, learning activities, especially at tertiary institutions in all zones, must be carried out online. Institution designs a distance learning system use the e-learning system. One of the Best Private Universities in Central Java, namely Dian Nuswantoro University, helped build a distance learning system, namely KULINO, which is a Moodle-based Learning Management System (LMS) in overcoming the Covid-19 Pandemic situation. This research aims to discover the social interactions that occur in online learning using KULINO. This study uses a qualitative research method with a phenomenological approach. Research results show interaction between students and lecturers in synchronous learning is more interactive. In contrast, the asynchronous learning interactions run in one direction so education is not interactive. The form of social interaction in online learning is associative in the form of cooperation and assimilation, while the form of dissociative interaction is in the form of conflict in the task group. Learning that is synchronously intertwined is more interactive, althought it must still be combined with asyncronous. Suggestions that can be given are that lecturers should be able to build interesting situations so that students are not bored and passive during online lectures.